Improved blood–brain-barrier permeability and tissue distribution following the oral administration of a food-grade formulation of curcumin with fenugreek fibre. (April 2015) - IM, Krishnakumar; Maliakel, Abhilash; G, Gopakumar; Kumar, Dinesh; Maliakel, Balu; Kuttan, Ramadasan
Highlights: A food grade water soluble formulation of curcumin with fenugreek dietary fibre. UPLC-ESI-MS/MS studies on rats for oral bioavailability and tissue distribution. Enhanced oral bioavailability and tissue distribution of free curcuminoids. Blood–brain-barrier permeability and pharmacokinetics of new formulation. Significant free unconjugated curcuminoids in plasma and tissues for longer duration. Abstract: The delivery of significant concentrations of biologically active free curcuminoids (curcumin, demethoxycurcumin and bisdemethoxycurcumin) at the target tissues has always been regarded as a major limitation for the efficacy of curcumin. Herein we report the blood–brain-barrier permeability, tissue distribution and enhanced bioavailability of free curcuminoids following the oral administration of a food grade curcumin formulation in comparison with the standardized native curcumin, for the first time. UPLC-ESI-MS/MS analyses of post-administration tissue samples of Wistar rats (200 mg/kg body weight) demonstrated significant ( p < 0.001) enhancement in plasma bioavailability (25-fold), in vivo stability and blood–brain-barrier permeability as evidenced from the tissue distribution of free curcuminoids at, (ng/g), brain (343 ± 64.7), heart (391.7 ± 102.5), liver (445.52 ± 83), kidney (240.1 ± 47.2), and spleen (229.72 ± 42.2), with extended elimination half-life of 3 to 4 h. Standard curcumin, on the other hand, detected only 1.4 ± 0.8 ng/g of curcumin in the brain tissues.